Paco: implementing Procrustean Approach to Cophylogeny in R. Issue 8 (27th February 2017) - Hutchinson, Matthew C.; Cagua, E. Fernando; Balbuena, Juan A.; Stouffer, Daniel B.; Poisot, Timothée
Summary: The concordance of evolutionary histories and extant species interactions provides a useful metric for addressing questions of how the structure of ecological communities is influenced by macro‐evolutionary processes. We introduce paco (v0.3.1), an R package to perform Procrustean Approach to Cophylogeny. This method assesses the phylogenetic congruence, or evolutionary dependence, of two groups of interacting species using both ecological interaction networks and their phylogenetic history. We demonstrate the functionality of paco through its application to empirical host‐parasite and plant‐pollinator communities. Although the package is intended to assess the phylogenetic congruence between groups of interacting species, the method is also directly applicable to other scenarios that may show phylogenetic congruence including historical biogeography, molecular systematics, and cultural evolution.